2007
DOI: 10.1111/j.1365-2443.2007.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast autophagy induced by nitrogen starvation generates a nitrogen source that drives adaptation processes

Abstract: Autophagy is a conserved bulk protein degradation process that is proposed to play a role in events that arise when organisms are forced to radically change their fate, including nutritional starvation, differentiation and development. In our present study, we have identified fission yeast autophagy as a bulk protein degradation process induced by the deprivation of environmental nitrogen, the effects of which are known to trigger sexual differentiation as an adaptive response. Autophagy-defective mutants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 49 publications
8
109
0
4
Order By: Relevance
“…Therefore, autophagy is also required for long-term survival in G0, though the degree is much less than proteasome function. This is consistent with the previous report (31).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, autophagy is also required for long-term survival in G0, though the degree is much less than proteasome function. This is consistent with the previous report (31).…”
Section: Resultssupporting
confidence: 83%
“…In fission yeast, it is demonstrated that autophagy contributes to the maintenance of cell viability upon nitrogen depletion (Kohda et al 2007). These reports prompted us to compare the growth of wildtype, Dtsc2, and Dnpr2 cells harboring the leu1-32 mutation upon nitrogen deprivation on YES plates.…”
Section: The Role Of Npr2 In the Regulation Of Autophagymentioning
confidence: 99%
“…23 Although GFP release from Atg8-GFP is a good measure of autophagic activity, this assay does not provide an insight into how dysfunctional autophagy affects the long-term survival of S. pombe. Hence, we next assessed the potential role of SpAtg10 in the long-term survival of nitrogen-starved cells.…”
Section: Resultsmentioning
confidence: 99%